REASON AND FEELINGS IN THE TREATISE OF MAN DURING THE AGE OF ENLIGHTENMENT - Edmundas Krakauskas (Problemos)
The mechanical view of this problem is characteristic of rationalists. D. Hume is more original and productive. His philosophical image of man is contradictory, but real. From this point of view, D. Hume and I. Kant are similar and the most interesting thinkers.